Elective orthopaedic cancellations due to the COVID-19 pandemic: where are we now, and where are we heading?. (February 2021) - Oussedik, Sam; MacIntyre, Sam; Gray, Joanne; McMeekin, Peter; Clement, Nick D.; Deehan, David J.
Abstract : Aims: The primary aim is to estimate the current and potential number of patients on NHS England orthopaedic elective waiting lists by November 2020. The secondary aims are to model recovery strategies; review the deficit of hip and knee arthroplasty from National Joint Registry (NJR) data; and assess the cost of returning to pre-COVID-19 waiting list numbers. Methods: A model of referral, waiting list, and eventual surgery was created and calibrated using historical data from NHS England (April 2017 to March 2020) and was used to investigate the possible consequences of unmet demand resulting from fewer patients entering the treatment pathway and recovery strategies. NJR data were used to estimate the deficit of hip and knee arthroplasty by August 2020 and NHS tariff costs were used to calculate the financial burden. Results: By November 2020, the elective waiting list in England is predicted to be between 885, 286 and 1, 028, 733. If reduced hospital capacity is factored into the model, returning to full capacity by November, the waiting list could be as large as 1.4 million. With a 30% increase in productivity, it would take 20 months if there was no hidden burden of unreferred patients, and 48 months if there was a hidden burden, to return to pre-COVID-19 waiting list numbers. By August 2020, the estimated deficits of hip and knee arthroplasties from NJR data were 18, 298 (44.8%) and 16, 567 (38.6%), respectively, compared to the same time period in 2019. The cost to clear this black log would be £198, 811, 335. Conclusion: There will be up to 1.4 million patients on elective orthopaedic waiting lists in England by November 2020, approximate three-times the pre-COVID-19 average. There are various strategies for recovery to return to pre-COVID-19 waiting list numbers reliant on increasing capacity, but these have substantial cost implications. Cite this article: Bone Jt Open  2021;2(2):103–110.